Betaine homocysteine methyltransferase (BHMT) as a specific and sensitive blood marker for acute liver injury. (November 2014) - Ma, Huailei; Ning, Jing; Jin, Xin; Mao, Chunming; Bu, Xiangli; Wang, Miao; Liu, Huan; Wang, Kun; Lausted, Christopher; Hood, Leroy; Chen, Jiankui; Hu, Zhiyuan
Abstract We developed a high-performance ELISA assay and measured serum BHMT levels in healthy individuals and patients with acute liver injury (ALI). The detection range of this ELISA assay was from 1.56 to 100 ng/ml. BHMT levels are significantly higher in ALI groups. In the healthy group (n = 244), the median value (interquartile range, IQR 0–56.40) was 1.83 ng/ml. In the ALI group (n = 42), the median value of BHMT was 748.48 ng/ml (IQR, 0–51095.92). ROC curve analysis demonstrated good sensitivity (0.86) and specificity (0.98). In addition, in five ALI cases with time course samples available, BHMT and ALT both followed the "rise and fall" temporal pattern with the disease progression. However, the slopes of BHMT curves were steeper than ALT curves. And in three out of the five cases, BHMT levels peaked 1 day earlier than ALT levels be a sensitive marker with good prognostic value.